Controlling the interaction via Feshbach resonances in a dual-species Bose-Einstein condensate: the implementation for potassium - Mazo, Pedro Luiz (2020)
In this work we document the first measure of Feshbach resonances in our laboratory utilizing potassium 39 in the state F = 1, mF = 0. We submitted the 39K atoms trapped in an optical trap to a homogeneous magnetic field in the range of up to 800 Gauss, where are expected resonances for the species in the |F = 1› manifold. Those are the first steps to come up with a machine capable of using this technique for different and innovative studies on superfluidity in a mixture of quantum gases. In our case, we use the same pair of coils both to obtain different magnetic field gradients (phase of MOT and MT), in anti-Helmholtz configuration, as well as to obtain a homogeneous magnetic field (tuning the magnetic field around previewed resonance), in Helmholtz configuration. To make this possible, we have implemented a H-Bridge system, which consists in installing one of the coils in a system of power switches. We have prepared the atomic cloud since the MOT, passing through a Gray Molasses stage and reaching our Optical Dipole Trap with 106 atoms at 12 μK where we apply a homogeneous field and perform a loss spectroscopy. Here we will present the resonances we have obtained and its characterization.